Genetic Engineering of Bacteriophages Against Infectious Diseases - Chen, Yibao; Batra, Himanshu; Dong, Junhua; Chen, Cen; Rao, Venigalla B.; Tao, Pan (Frontiers in Microbiology, 2019)
Bacteriophages (phages) are the most abundant and widely distributed organisms on Earth, constituting a virtually unlimited resource to explore the development of biomedical therapies. The therapeutic use of phages to treat bacterial infections (“phage therapy”) was conceived by Felix d’Herelle nearly a century ago. However, its power has been realized only recently, largely due to the emergence of multi-antibiotic resistant bacterial pathogens. Progress in technologies such as high-throughput sequencing, genome editing, and synthetic biology further opened doors to explore this vast treasure-trove. Here, we review some of the emerging themes on the use of phages to treat infectious diseases. In addition to phage therapy, phages have also been developed as vaccine platforms to deliver antigens as part of virus-like nanoparticles that can stimulate immune responses and prevent pathogen infections. Phage engineering promises to generate phage variants with unique properties for prophylactic and therapeutic applications. These approaches have created momentum to accelerate basic as well as translational phage research and potential development of therapeutics in the near future.